Convergent evolution in Arabidopsis halleri and Arabidopsis arenosa on calamine metalliferous soils. (3rd June 2019) - Preite, Veronica; Sailer, Christian; Syllwasschy, Lara; Bray, Sian; Ahmadi, Hassan; Krämer, Ute; Yant, Levi
Abstract : It is a plausible hypothesis that parallel adaptation events to the same environmental challenge should result in genetic changes of similar or identical effects, depending on the underlying fitness landscapes. However, systematic testing of this is scarce. Here we examine this hypothesis in two closely related plant species, Arabidopsis halleri and Arabidopsis arenosa, which co-occur at two calamine metalliferous (M) sites harbouring toxic levels of the heavy metals zinc and cadmium. We conduct individual genome resequencing alongside soil elemental analysis for 64 plants from eight populations on M and non-metalliferous (NM) soils, and identify genomic footprints of selection and local adaptation. Selective sweep and environmental association analyses indicate a modest degree of gene as well as functional network convergence, whereby the proximal molecular factors mediating this convergence mostly differ between site pairs and species. Notably, we observe repeated selection on identical single nucleotide polymorphisms in several A. halleri genes at two independently colonized M sites. Our data suggest that species-specific metal handling and other biological features could explain a low degree of convergence between species. The parallel establishment of plant populations on calamine M soils involves convergent evolution, which will probably be more pervasive across sites purposely chosen for maximal similarity in soil composition. This article is part of the theme issue 'Convergent evolution in the genomics era: new insights and directions'.